“Eina ” el tejer y des-tejer de una maestra - Escorcia Romero, Tadiana Guadalupe (Educación y Ciudad, 2019)
In these pages a piece of the path of a teacher whose path has been surrounded by infants and families from different contexts is woven. Such a course configures the essence of being a teacher, each pedagogical scenario demarcates the course to innovate and investigate from and with the community, empowering education, pedagogy and the lives of those who converge there. Likewise, those school, social and pedagogical tensions that appear along the way, much more when there is diversity of ethnic groups, knowledge, origins, and how they constitute a support to dignify the community voice.